A new Lepidoblepharis lizard (Squamata: Sphaerodactylidae) from the Colombian Guyana shield - Calderón-Espinosa, Martha Lucia; Medina-Rangel, Guido Fabian (Zootaxa, 2016)
Lepidoblepharis lizards are tiny geckos of the forest leaf litter. This genus is distributed from Nicaragua to the Amazonian region of Peru and Brazil, and the genus currently contains 21 species. We found a new small Lepidoblepharis from eastern Colombia that we here describe as a new species. It is characterized by having granular or subconical dorsal scales; 10–13 subdigital lamellae under 4th toe; postmental border slightly or strongly projecting backwards, followed by 2–5 (usually 3) postmentals; and 20–31 scales across snout at lst/2nd supralabial suture. This new taxon is compared to all congeners.